Developing assertiveness skills for health and social care professionals - Phillips, Annie (Radcliffe Publishing, 2013)
This highly practical guide, and its companion volume Developing Leadership Skills for Health and Social Care Professionals is a tool for all health and social care professionals wanting to develop relationships with their colleagues, patients and clients including clinicians, practice managers, nurses, midwives, general practitioners, therapists, doctors, dieticians, psychological therapists, paramedics and health visitors